The Role of Public Relations Departments In Enhancing The Image of Jordanian Ministries - Ali Yahya, Bader Al-Hadeed
The primary focus of modern public relations managers is to gain publics' loyalty and cushion the organization against negative publicity in future. Image is an organizational asset that plays a critical role in enhancing publics' loyalty and organizational success. The primary purpose of this study was, therefore, to identify the current image of Jordanian ministries , and suggest ways in which public relations departments within government ministries in Jordan can enhance the image of the ministries among their internal publics. The study adopted a mixed methods design and conducted according to Organizational Image Configuration Method developed by Schuler (2004) which is grounded in the cognitive attribution theory. Participants (14 for qualitative phase; 383 for quantative phase) were employees of the Ministry of Youth and Sports and the Ministry of Interior in Jordan. From the qualitative phase, 29 image attributes were identified. They were increase to 52 following a review of literature in order to include all known organizational image attributes in the questionnaire. Attributes that scored high on importance but scored low on satisfaction were considered as the most critical in building the image of the ministries. A factor analysis using principal components analysis with varimax rotation was performed to discover the underlying structure represented by the attributes. The 52 attributes substantainlly loaded onto six factors which were named System and Quality. Human Resource Management, Mangement, Significance of Job and Appraisals, Strenght of Communcation and Physical Work Environment. Findings show that employees want to be more autonomous, independent, and flexible in order to realize their full potentials. The importance of evaluation systems was identified as key in developing a favorable image of the Jordanian government ministries. Despite the efforts made by the Jordanian government to reform and modernization. The findings underlined the need for the PR managers in government to control the publicity that government ministries receive in order to influence the building of a favorable image. Jordanian government employees believe that they are not receiving remuneration that matches the value of the work they do. The PR function needs to work with the human resource department and the management to enhance the working conditions of the employees. Furthermore, the study showed that clearly defined goals and commitment of employees are crucial attributes in enhancing the image of the Jordanian ministries. PR departments are required to reconcile organizational goals with the expectations of the organization's publics in order to enhance the image of the organization. For public relation officers, the basic strategy to improve the image of the ministries is to focus on those factors with more attributes close to the nucleus of the graph. In addition, special attention should be given to the attributes that scored high on importance but scored poorly on satisfaction. The study has shown that Shuler's model, grounded in the cognitive attribution theory , can be used to study and suggest ways to build and develop the image of government ministries. This study has also stressed the importance of power and influence in public relations. Future studies might consider study the image of Jordanian government ministries from the perspective of external publics. Additionally, there will be need to conduct multiple interviews with different groups of ministry employees in order to identify an exhaustive number of image attributes.